2013
DOI: 10.1177/000348941312200708
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation of Respiratory Papillomatosis in a Solid-Organ Transplant Patient: Case Report and Literature Review

Abstract: We report the case of a 77-year-old non-smoker and non-drinker with a solid-organ transplant who had malignant transformation of respiratory papillomatosis 3 years after the initial diagnosis of this benign lesion. This is the first case reported in the literature of malignant transformation of respiratory papillomatosis in a solid-organ transplant patient. Virus-associated cutaneous cancers occur more frequently and aggressively in solid-organ transplant patients. There may be a higher rate of malignant trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Gastroesophageal reflux and immunosuppression may also be aggravating factors for patients with papillomatosis [15, 16]. In the present case, no signs of reflux or immunosuppression were found.…”
Section: Discussionmentioning
confidence: 42%
“…Gastroesophageal reflux and immunosuppression may also be aggravating factors for patients with papillomatosis [15, 16]. In the present case, no signs of reflux or immunosuppression were found.…”
Section: Discussionmentioning
confidence: 42%
“…Bronchoscopic pictures were suggestive of papillary lesion although association with HPV can't be commented upon as patient refused for further testing. A literature review of RRP case reports revealed that patients usually have the diagnosis of RRP many years before evidence of malignant transformation (9)(10)(11)(12). In contrast, our patient had evidence of malignant transformation about six months after diagnosis of respiratory papillomatosis.…”
Section: Discussionmentioning
confidence: 57%
“…The higher risk of carcinoma reported in elderly patients can be related to genetic susceptibility contributing to the phenotype [ 13 , 23 ]. The association of malignancy and immunosuppressive therapy is mediated through several pathogenic direct and indirect factors [ 24 , 25 ]. Therefore, the dose of immunosuppression shall be adjusted carefully to reduce the risk of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%